Development of gamma ray scanning coupled with computed tomographic technique to inspect a broken pipe structure inside laboratory scale vessel - Dhanaj Saengchantr; Somyot Srisatit; Nares Chankow (Nuclear Engineering and Technology, 2019)
This paper presents a laboratory experiment on data acquisition technique that applied to the gamma radiation scanning coupled with computed tomography (CT) technique for inspection of broken nozzle inside the vertical vessel. The acquisition technique was developed to inspect a large diameter vessel when suspicious problem location is not easily accessed. This technique allows the installation of gamma radiation source (Cesium 137, Cs-137), and detectors (Sodium Iodine. NaI(Tl)) from the accessible location to the required location and performs the scanning by designed pattern. To demonstrate the designed technique, top opened tank which installed with six cut steel pipes diameter of 76.2 mm (3'') at a certain position was selected. They were assumed to be a gas riser pipes inside the vessel. Three studied cases were performed, (a) projection of well installed six pipes, (b) projection of one out of six broken pipe and (c) one of nozzle was assumed to be failure and fell down until one out of six pipes was broken and obstructed by nozzle. Results clearly indicated the capability of developed technique to distinguish between normal situation case and abnormal situation cases. Keywords: Industrial computed tomography, Vessel inspection, Gamma transmission, On-line inspection, Nozzle inspection